2019
DOI: 10.1021/acs.cgd.9b00219
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Cocrystallization—An Enabling Technology for the Development of High Dose Direct Compression Tablets of Poorly Soluble Drugs

Abstract: Spherical cocrystallization (SCC), an integrated crystal and particle engineering approach, was successfully applied to generate spherical cocrystal agglomerates (SCA) between a poorly soluble drug, griseofulvin (GSF) and acesulfame (Acs). The SCC process consists of two steps: (1) GSF-Acs cocrystal formation by reaction crystallization in a slurry; (2) agglomeration by adding a bridging liquid. The obtained SCA exhibited superior mechanical and powder properties over GSF. Inclusion of a small amount (<1%) HPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…83 In another clear example of the impact of changes in physical properties, morphology modification brought about by crystallization in the presence of hydroxypropyl cellulose polymer yielded improved compactability of the API. 8,84 Another study showed levels of polymer of 0. resulted in composite particles with improved API physical properties, while higher levels of polymer (∼9−12 wt %) stabilized a kinetic crystalline phase. 26 Work has also shown changes in morphology between rods and rectangular plates along with beneficial effects on compactability.…”
Section: ■ Routes To Generate Co-processed Apimentioning
confidence: 99%
See 2 more Smart Citations
“…83 In another clear example of the impact of changes in physical properties, morphology modification brought about by crystallization in the presence of hydroxypropyl cellulose polymer yielded improved compactability of the API. 8,84 Another study showed levels of polymer of 0. resulted in composite particles with improved API physical properties, while higher levels of polymer (∼9−12 wt %) stabilized a kinetic crystalline phase. 26 Work has also shown changes in morphology between rods and rectangular plates along with beneficial effects on compactability.…”
Section: ■ Routes To Generate Co-processed Apimentioning
confidence: 99%
“…Pharmaceutically acceptable additives have demonstrated the ability to alter API crystal form, ,, morphology, , surface features, nucleation, , and supersaturation relief/growth rate. , In one case, the ability to impact API and not impurity supersaturation relief kinetics allowed for greater impurity rejection . In another clear example of the impact of changes in physical properties, morphology modification brought about by crystallization in the presence of hydroxypropyl cellulose polymer yielded improved compactability of the API. , Another study showed levels of polymer of 0.4–5 wt % altered morphology and resulted in composite particles with improved API physical properties, while higher levels of polymer (∼9–12 wt %) stabilized a kinetic crystalline phase . Work has also shown changes in morphology between rods and rectangular plates along with beneficial effects on compactability .…”
Section: Routes To Generate Co-processed Apimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the greatly enhanced powder properties of the spherical products achieve advanced functions, for example, direct tableting for drugs, 9–12 anti‐caking ability for food and fertilizers, 13 superior skin feeling for cosmetics, 14 high performance for explosives, 15–17 and so on. In addition, spherical agglomeration technology improves the efficiency of downstream product handling in most cases, for example, washing, filtration, drying, and others 18–20 …”
Section: Introductionmentioning
confidence: 99%
“…Cocrystallization is a crystal engineering technique widely used in pharmaceutical research and the development of drugs [3,4]. It exploits non-covalent interactions between neutral or ionic components with a defined stoichiometry in a solid-state structure [5], which could improve the physicochemical properties of active pharmaceutical ingredients (API), including solid-state stability, such as sublimation tendency and hydration tendency [6,7], solubility [8] and dissolution [9], mechanical properties [10], permeability [11], and punch sticking propensity [12,13].…”
Section: Introductionmentioning
confidence: 99%